ANALISIS IMPLEMENTASI PROGRAM MAKAN BERGIZI GRATIS PADA KELOMPOK B DI TK ISLAM LUTFIAH OGAN ILIR - Tri Ayu Wulandari; Akbari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the implementation of the Free Nutritious Meals Program (MBG) in Group B at Lutfiah Islamic Kindergarten in Ogan Ilir. This study employs a descriptive qualitative approach, utilizing data collection techniques such as observation, interviews, and documentation. Data analysis utilized the Miles and Huberman model, which includes data collection, data reduction, data presentation, and drawing conclusions. The results of the study indicate that the implementation of the Free Nutritious Meal Program (MBG) has been carried out through the planning, implementation, and evaluation stages. During the planning stage, the school coordinated with the food provider (SPPG) and parents, and prepared supporting facilities such as dining areas, handwashing stations, and trash bins. During the implementation phase, group meals were conducted in a structured manner with teacher supervision and the promotion of clean living habits, such as handwashing before and after meals. However, it was found that children’s acceptance of the food varied; while some children enthusiastically consumed the MBG meals, others preferred packed lunches from home due to food preference factors. In addition, parents’ responses to this program have generally been positive because it helps meet children’s nutritional needs, although there are some challenges, such as ensuring the menu aligns with children’s tastes. Thus, the implementation of the Free Nutritious Meals Program (MBG) has been quite successful, but it remains influenced by factors such as children’s preferences and parental support.